Straddling the nonformal and formal education paradigm: a qualitative study of transformative learning within an Islamic Teacher Education Programme presented in the Western Cape from 2012 to 2014 - Jacobs, Yasmina (School of Education, 2017)
This study addresses the question of the transformative effect of a nonformal learning programme for Muslim education practitioners - the Islamic Teacher Education Programme (ITEP) in the Western Cape, within the context of lifelong learning. It investigates the effect on participants' personal teaching practice and whether it assisted adult learners with decisions for further formal study. ITEP can be treated as an example of a wide variety of nonformal programmes within different contexts. The programme serves to fill the gap where no accommodation is afforded to it in the broader formal education provision of this country. This dissertation argues that nonformal education has the ability to be a springboard to launch educators on a trajectory of personal transformation and development in their own field of practice, as well as to forge a path that provides access to formal education. A qualitative research design and a narrative research method was utilised to answer the research question, drawing on a range of data - personal learning narratives of adult learners; interviews with a sample of six learners as well as journal entries. This approach allowed the study to demonstrate how participants gauged the readiness for change in their own transformative perceptions from their personal learning experiences in a safe environment. The spaces created within the programme created the opportunity for participants to reflect critically, participate and collaborate in a range of learning experiences that served as a catalyst for perspective transformation. The six participants of this study revealed how disorienting dilemmas, frame of reference and context are important to consider in programmes such as the ITEP. The research has shown that the provision of competent educators to teach, motivate and inspire is possible by means of teacher training in faith-based, indigenous and other non-western, nonformal spaces with a group of nonformal practitioners that generally do not have any access to formal higher education. While such a programme is rarely considered by policy efforts, it certainly does not diminish the legitimate role the programme plays and the value placed on it by the society which it serves.